THE CHALLENGES OF WESTERN THOUGHTS IN INDONESIA: A Study of Centre For Islamic And Occidental Studies (CIOS) Role - Armayanto, Harda; Hutama Al Faruqi, Achmad Reza; Salsabila Zain, Naura Safira (State Islamic University North Sumatra, 2023)
Abstract: Westernization seems to have affected the way Indonesian society thinks. This is evidenced by the identity and character crisis as well as a lifestyle that is slowly starting to ignore spiritual elements. In response to this, Universitas Darussalam Gontor (UNIDA) took an important step by establishing the Center for Islamic and Occidental Studies (CIOS) which focuses on the study of Islam and occidentalism. This article analyzes the role of CIOS in achieving the goal of restoring Islamic civilization. This research uses a qualitative method with a case study approach. Data collection was conducted through books, journals, and media related to the topic. The study found that westernization significantly affected the intellectual and political aspects of Indonesian society.Keywords: CIOS, Occidentalism, westernisation, orientalism, Islamic civilization.